Differences in Sexual Identity Dimensions between Bisexual and Other Sexual Minority Individuals: Implications for Minority Stress and Mental Health - la Roi, Chaïm (Am J Orthopsychiatry, 2018)
Bisexual individuals experience poorer mental health than other sexual minority individuals. One explanation for this is that biphobia predisposes bisexual individuals to have a more ambiguous sexual identity and fewer opportunities for stress-ameliorating forms of coping and support. This study explores sexual identity and sexual identity dimensions—prominence, valence, integration, and complexity—in bisexual and other sexual minority individuals. We describe differences in sexual identity dimensions between bisexual and other sexual minority individuals and test two explanations for mental health disparities between them: whether sexual identity dimensions directly impact mental health and whether they moderate the impact of stress on mental health. Data came from a longitudinal study of a diverse sample of sexual minority individuals (N = 396, 71 bisexual respondents) sampled from community venues in New York City. Sexual identity was prominent for both bisexual and other sexual minority individuals, but bisexual individuals reported lower valence and integration of sexual identity in their identity structures. The hypothesis that sexual identity dimensions moderate the impact of minority stress on mental health was not supported. Following several longitudinal assessments, however, we concluded that identity valence (but not integration or complexity) and depressive symptoms were bi-directionally associated so that differences in valence between bisexual and other sexual minority individuals explained, in part, disparities in depressive symptoms.